Analysis of Moldova's built cultural heritage with commercial potential - Maria-Liliana, Marian (Technium Business and Management, 2023)
Cultural heritage is an ideal resource for sustainable development, provided it is harnessed. In this article, the author presents the analysis of the built heritage from the point of view of the number of monuments in geographical profile, the structure of the monuments built according to their functional destination and the possibility of their use, emerging from the market analysis. The author also analyzes the economic and financial opportunities for safeguarding the cultural heritage built in the Republic of Moldova. The issues facing the built heritage segment include: the legal and technical regulatory issues; the technical aspects with reference to the specific materials of the restoration works and the special construction technologies correlated with the conditions characteristic of the area. The main problems refer to the lack or insufficiency of financial means for the rehabilitation and inclusion in the economic circuit of the built heritage, preserving its cultural value.